A RESTful and semantic framework for data integration. (29th April 2014) - Fuentes‐Lorenzo, Damaris; Sánchez, Luis; Cuadra, Antonio; Cutanda, Mar
Summary Companies have to deal with huge amounts of heterogeneous information, usually stored in distributed datasets that make use of different data schemas. This topic is especially crucial for enterprises that deal with new and different kinds of business data as new services are provided; they need to be able to dynamically add new datasets with new schemas to their information systems. However, even though research efforts have been applied to deal with this integration problem, there is still a lack of practical approaches ready to be implemented for industrial cases. We present a web‐based architecture and system built upon ontologies and other semantic web techniques to cope with federation of business data in real time. The scenario used to demonstrate the utility of the architecture is composed of actual data of a telecom company. Results show that our solution is more suitable, efficient and practical than other works. Copyright © 2014 John Wiley & Sons, Ltd.